Asymptotic stabilization of a flexible beam with an attached mass - Kalosha, J. I.; Zuyev, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.977A mathematical model of a simply supported Euler – Bernoulli beam with attached spring-mass system is considered. The model is controlled by distributed piezo actuators and a lumped force. We address the issue of asymptotic behavior of solutions of this system driven by a linear feedback law. The precompactness of trajectories is established for the operator formulation of the closed-loop dynamics. Sufficient conditions for strong asymptotic stability of the trivial equilibrium are obtained.